THE RELATIONSHIP BETWEEN UNDERSTANDING OF ABILITY TO PROBLEM SOLVING CONCEPTS PHYSICAL CAPABILITIES FORM ABSTRACT STUDENT CLASS X SMA NEGERI 1 ANGKOLA BARAT - Henry Dinus Hutabarat; Ferawati Artauli Hasibuan (Jurnal Pendidikan Fisika, 2019)
Has done research for the purpose of to determine Has done research for the purpose of to determine the relationship between the understanding of the concept of students with the ability to solve problems of Newton's laws class X student of SMA Negeri 1 Angkola Barat in the academic year 2017, the second, to determine how much stronger relationship understanding of the concept with the ability to solve problems of Newton's laws class X SMA Negeri 1 Angkola Barat in the academic year 2017, the third, to know how big contribution to the understanding of the concept of the ability to solve problems of newton's laws of class X student of SMA Negeri 1 Angkola Barat in academic year 2017. This research was conducted in SMA Negeri 1 Angkola Barat with the population of all students in class X IPA at SMAN 1 Angkola Barat and a sample was taken 30 students of class X IPA 2 by using purposive sampling mehtod. Research using correlation method and data were analyzed by statistical methods. The study used a data collection tool that tests Understanding Concepts and Problem Solving Ability Test Physics. The study used data collection tool is calibrated through validity and reliability test. The results of the study there is a relationship between students' understanding of the concept with the ability to solve problems of Newton's laws of class X student of SMA Negeri 1 Angkola Barat Academic Year 2017. After koefien consult with the correlation table "r" of Pearson Product Moment, turned out rhit > rtab. Both at the level of 0.01 (1%) and 0.05 (5%), ie 0.975> 0.361 and 0.975> 0.463. While, testing the significance turns thit > ttab ie 23.44> 1.9958. While, the contribution of variable X to variable Y by 95.06%.